Topical corticosteroids minimise the risk of postinflammatory hyperpigmentation after ablative fractional Co2laser resurfacing in Asians - K. Nutjira Cheyasa (2018)
© 2015 Acta Dermato-Venereologica. Postinflammatory hyperpigmentation (PIH) is the most common adverse effect of laser treatment in dark-skinned individuals. Little is known whether PIH can be prevented or minimised. The objective of this study was to investigate the effect of short-term application of topical corticosteroids on the incidence of PIH after ablative fractional resurfacing in Asians. Forty subjects with skin phototype IV and atrophic acne scars were treated with a fractional CO2laser on both sides of the face. Post-operatively, clobetasol propionate 0.05% ointment was applied to one randomly selected side of the face for the first 2 days, followed by an application of petrolatum jelly for the rest of the week (petrolatum was applied to the other side for 7 days). Assessments on the clinical outcome, the wound healing process and the occurrence of PIH were obtained once weekly for the first month and at 2 and 3 months post-treatment. The side of the face treated with petrolatum alone had significantly (p < 0.001) higher incidence of PIH (75%) after laser irradiation than the side of the face treated with topical corticosteroids and petrolatum (40%). The PIH occurring on the petrolatum-treated sides had significantly higher intensity (p < 0.001) and was spread over a significantly larger area (p < 0.001), compared with the corticosteroid-and petrolatum-treated sides. In conclusion, a short-term application of topical corticosteroids postoperatively is associated with a decreased risk of PIH after ablative fractional resurfacing.